2011
DOI: 10.1038/ejcn.2011.127
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of intake of plant-based foods with 6-n-propylthiouracil sensitivity and food neophobia in Japanese preschool children

Abstract: Background/Objectives: Diets rich in plant-based foods such as vegetables, fruits and soy foods have been suggested to have beneficial effects on health. However, phytochemicals contained in plant-based foods are generally bitter and acrid. We investigated whether intake of vegetables, fruits and soy foods is associated with sensitivity to bitterness and reluctance to eat new foods (food neophobia) in Japanese preschool children. Subjects/Methods: Subjects of this cross-sectional study were healthy Japanese, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…A similar relationship has previously been established in children by many studies (2,(16)(17)(18)(19)(20)(21) . However, we investigated the associations beyond correlations and also provided quantitative estimates for the differences between food neophilics (FNS score 10-24) and food neophobics (FNS score 40-70).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…A similar relationship has previously been established in children by many studies (2,(16)(17)(18)(19)(20)(21) . However, we investigated the associations beyond correlations and also provided quantitative estimates for the differences between food neophilics (FNS score 10-24) and food neophobics (FNS score 40-70).…”
Section: Discussionsupporting
confidence: 51%
“…Unsurprisingly, food neophobia restricts the variety of one's diet (13)(14)(15) , but the effects of neophobia on the consumed amounts of specific foods are less obvious. In children, however, several studies have shown that high food neophobia is associated with low consumption of fruit and vegetables (16)(17)(18)(19)(20) or specifically vegetables (2,21) . Results from the studies that measured consumption of fruit and vegetables separately (16,17,19,21) suggest that child food neophobia correlates more strongly with vegetable intake than with fruit intake.…”
Section: Food Neophobia Diet Quality Steps Study Vegetable Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies that have found differences between dietary intake as a function of PROP status have utilized food frequency questionnaires (77,78) or measured ad libitum intake (15,54,75). Most studies that have used self-report diet recalls or food diaries have not seen any relationship with PROP status (5,22,50,101,102,134). The biases inherent in methods for dietary reporting have been thoroughly discussed, and all methods have obvious strengths and limitations.…”
Section: Conclusion and Directions For Future Studiesmentioning
confidence: 99%
“…These methods have well-known biases but are often the only practical means of estimating intake, particularly for large populations. In 323 children ages 4 to 6 from Japan, nontaster boys reported higher intake of soy-containing foods on a three-day food record compared with taster boys, but only food neophobia, and not PROP status, predicted vegetable intake in this cohort (134). In the Irish cohort from Feeney and colleagues (50), children who had the AVI/AVI nontaster genotype reported higher intake of folate, a nutrient found in green leafy vegetables, compared to children who had taster haplotypes.…”
Section: Bitter-and Strong-tasting Foodsmentioning
confidence: 99%